EFFECT OF SUPPLEMENTARY IRRIGATION SYSTEM ON WHEAT PRODUCTION EFFICIENCY USING A STOCHASTIC FRONTIER ANALYSIS - Ali, E. H.; Baker, Y. T.; Al-Douri, B. F. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study was aimed to director wheat production's technical efficiency grown under two irrigation systems(fixed and pivot sprinkler irrigation systems)using random border analysis.Samples were collected randomly from267farmers from Salah Al-Din Governorate/Iraq.The samples were divided into two groups;187farmers used a pivot sprinkler irrigation system with three categories of possession(80,60and120dunums),while the other group used a fixed sprinkler irrigation system with four categories of possession(40,30,20and10dunums).Transcendent production function was used to study the effect of production factors on wheat yield. The results indicated that the mechanization work and the amount of added irrigation water increased by 1% while the wheat yield increased by0.08and0.15%,respectively.The pivot sprinkler irrigation system's technical efficiency averaged0.86,while the fixed sprinkler irrigation system's efficiency was0.84.The technical efficiency and experience increased with the farmers' experience with supplementary irrigation, the cultivated area and age. On the other hand, technical efficiency and experience decreased with the family's size and wheat cultivating experience. Furthermore, farmers who owned mechanization were more efficient than the lessors. The sprinklers' highest productivity was in the pivot sprinkler irrigation system at120dunums and was 108,930 kg. The highest productivity per water unit was0.86in the fixed sprinkler irrigation system of10 and 40 dunums. The efficiency of water use was 86% when the cultivated area was120dunums with the pivot sprinkler irrigation system and87% at40 dunums with the fixed sprinkler irrigation system.